2014
DOI: 10.1007/s11999-013-3128-y
|View full text |Cite
|
Sign up to set email alerts
|

Knee Moments After Unicompartmental Knee Arthroplasty During Stair Ascent

Abstract: Background For unicompartmental knee arthroplasty (UKA), abnormal loading on the tibiofemoral joint could exacerbate knee osteoarthritis or implant wear. Joint moments are an indirect measure of such loading. However, little is known about knee moments of patients with UKA, tempering enthusiasm for its use. Questions/purposes In patients with UKAs performing stair ascent, we (1) determined whether interlimb differences for knee moments are demonstrated, (2) described the knee kinetics of patients with medial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The main described difference concerned the varus-valgus movement [ 23 , 24 ]. The varus rotation in flexion was decreased significantly [ 25 , 26 ], with the loss of lateral laxity in flexion [ 23 ]. With a morphometric implant, we found restoration of the preoperative varus-valgus movement over the full range of motion, with preservation of the physiological lateral laxity in flexion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main described difference concerned the varus-valgus movement [ 23 , 24 ]. The varus rotation in flexion was decreased significantly [ 25 , 26 ], with the loss of lateral laxity in flexion [ 23 ]. With a morphometric implant, we found restoration of the preoperative varus-valgus movement over the full range of motion, with preservation of the physiological lateral laxity in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In cadaver studies, the knee motion after UKA has been described close to normal [ 8 , 10 ], but when performed in vivo, the results were sometimes less obvious [ [22] , [25] , [26] , [27] ]. An in vitro assessment with more complex movements is thus interesting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study 27 showed that although some abnormalities persisted in muscle activity around the knee, a good restoration of gait was achieved by most unicompartmental knee patients independently of the UKA design. Multiple UKA gait scene such as stair ascent, 28 downhill walking, 29 and on a level and sloped grounds 30 have been studied to demonstrate the biomechanical characteristics of UKA.…”
mentioning
confidence: 99%